2008
DOI: 10.1101/lm.904308
|View full text |Cite
|
Sign up to set email alerts
|

Intra-amygdala injections of CREB antisense impair inhibitory avoidance memory: Role of norepinephrine and acetylcholine

Abstract: Infusions of CREB antisense into the amygdala prior to training impair memory for aversive tasks, suggesting that the antisense may interfere with CRE-mediated gene transcription and protein synthesis important for the formation of new memories within the amygdala. However, the amygdala also appears to modulate memory formation in distributed brain sites, through mechanisms that include the release of norepinephrine and acetylcholine within the amygdala. Thus, CREB antisense injections may affect memory by int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 93 publications
(110 reference statements)
1
17
1
Order By: Relevance
“…Studies by the groups of McGaugh, Izquierdo, and other authors suggest that the release of NA in the basolateral amygdala play a critical role in the memory consolidation of aversive tasks (McGaugh 2004;Canal et al 2008;Chamberlain et al 2006;Izquierdo et al 1992;Roozendaal et al 2008). Therefore, it is not surprising that, in the present study, the only significant alteration observed in the amygdala of the rats treated with NaF was a decrease in DHPG, a metabolite of NA.…”
Section: Daily Food Consumption (G)contrasting
confidence: 39%
“…Studies by the groups of McGaugh, Izquierdo, and other authors suggest that the release of NA in the basolateral amygdala play a critical role in the memory consolidation of aversive tasks (McGaugh 2004;Canal et al 2008;Chamberlain et al 2006;Izquierdo et al 1992;Roozendaal et al 2008). Therefore, it is not surprising that, in the present study, the only significant alteration observed in the amygdala of the rats treated with NaF was a decrease in DHPG, a metabolite of NA.…”
Section: Daily Food Consumption (G)contrasting
confidence: 39%
“…The question arises, however, whether these treatments also have their actions on memory by their intended actions or by resulting in altered neurotransmitter functions that underlie the memory impairments. In a recent study, we found that CREB antisense treatment administered 6 h before training resulted in memory impairments assessed 48 h after training (Canal et al 2008). The antisense treatment also reduced training-initiated release of NE release; injections of clenbuterol, a b-adrenergic receptor agonist, at the time of training reversed the amnesia.…”
Section: Discussionmentioning
confidence: 99%
“…9 10 Acetylcholine and NE are excitatory neurotransmitters implicated in memory mechanisms. 11 Moreover, hippocampal activation of nAChRs stimulates NE release 12 and facilitates long-term potentiation. 13 As heterologously expressed neuronal nAChRs are highly sensitive to IAs at subanaesthetic concentrations, 14 15 we determined the effects of isoflurane on NE release as a potential neurochemical model for the amnesic effects of IAs.…”
mentioning
confidence: 99%